HUMAN RIGHTS TO PROTECTION IN MILITARY CONFLICT AND MARTIAL STATE: KEY ISSUES - IVANIUK, RUSLAN (Ehrlich's Journal, 2023)
This article analyzes the issue of the human right to protection in the context of military conflict and martial law. It is established that human rights and the right to their protection are regulated by both national and international law, the purpose of which is to systematically control the implementation of obligations to comply with international universal principles and international legal norms, and to apply legal enforcement measures for their violation. It is emphasized that in the context of military conflict and under martial law, international legal protection of human rights should be considered as a set of norms defined by international legal instruments and national legislation aimed at protecting universally recognized civil, political, economic, social, cultural, and other human rights and freedoms from unlawful infringements. The author notes that human rights restrictions in the context of military conflict and martial law should be differentiated from human rights violations since they are two different political and legal categories by nature and function. Restriction of human rights occurs when, in accordance with the goals defined by law, the State or its authorized entities restrict certain potential human capabilities in the context of the legal field – ensuring public security, protection of public order, health care, protection of rights and freedoms of other persons or interests of society as a whole. Instead, violations of human rights and freedoms are a priori beyond the legal framework. It is emphasized that restriction of fundamental human rights and freedoms is possible only as an exclusively legal, temporary, nondiscriminatory phenomenon and consists in reducing the scope and content of human rights only in general in the interests of the security of society and the State. It is emphasized that the problem of human rights protection in the context of military conflict and under martial law in Ukraine is also due to the fact that because of the temporary occupation of some Ukrainian territories and active hostilities, the courts in some regions ceased to function, and, as a result, the protection of rights was not carried out by the courts, so it to ensure the normal functioning of the judiciary that the current legislation was amended.